Caracterización de la mastofauna, en estribaciones de la cordillera occidental de los andes en los bosques montano, piemontano y montano bajo, sector el Tingo la Esperanza, COTOPAXI 2019 – 2020. - Carrera Cisneros, Marco David (2020)
This research was to obtain information on the Mastofauna in the Montano, Piemontano and Montano forests in the parish of the Tingo la Esperanza sector, Los Laureles and Chugchilán, where the foothills of the Andes mountain range are located, in the zoogeographic floor Western and temperate subtropical. The information collected is part of the research carried out in the study area, using as reference books of mammals, scientific articles, etc. This researching depend on inventory guides of wildlife and Mastofauna of Ministerio del Ambiente. The methods used were observation, Trick cameras, Sherman traps and mist network, none of these methods were adjusted to a rigorous design or pre-established sampling time. In addition, none of these methodologies used causes damage to the different affected species in the study areas. From October 2019 to February 2020, 32 species were registered, belonging to 7 orders that are: Rodentia, Chiroptera, Primates, Carnivora, Cingulata, Artiodactyla and Didelphimorphia, of these orders make up 20 families in which 2 are endemic to the western subtropical floor , have high sensitivity to habitat alteration, 20 have medium sensitivity and 19 have low sensitivity. Likewise 5 species are in some threat category; 4 in almost threatened (NT) and 1 vulnerable (V). This area has been little explored and studied, its Mastofauna is just beginning to be known, however the diversity and abundance found between 600 and 3100 meters above sea level is highest. These are deeper studies and with standardized methods to know details of these communities of mammalian species.